Psychologies of the Social-Organizational Area in Peru: 2003-2012 - León, Federico (2013)
This article assesses four subdisciplines of Peruvian psychology. Organizational psychologists face the challenge of adjusting their good practices to scientific evidences; those studied in the United States or Europe are not necessarily relevant to all types of Peruvian organizations and populations. Consumer psychology has achieved popular impacts, but practitioners, either qualitative or quantitative, do not disseminate their methods and findings with rigor. Community psychologists’ contributions could improve if their hypotheses originated in psychoanalysis or other perspectives were formulated with clarity and tested by means of conventional techniques designed for the evaluation of interventions. Peruvian social psychology is contributing to the understanding of national realities and has generated original findings concerning poverty reduction, national identity, personal wellbeing, and effects of geography.